Optimalisasi Tekanan Vakum dan Massa Pada Proses Freeze Drying Terhadap Kadar Air Ikan - Taufik Dwi Putra; Widjanarko (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
Many fishery products come from fishing and cultivation, saltwater and freshwater fisheries, so a preservation process is needed to maintain the condition of the fish so that it remains good when marketed. In addition, it can increase the economic value of fish. In the Indonesian fisheries industry, various types of preservation, including freeze drying, are drying processes using vacuum pressure and cold temperatures. The freeze-drying process utilizes the phased nature of water to convert solid (frozen) forms into water vapor (gas) at a certain pressure and temperature. The vacuum pressure used ranges from -60.3 cmHg to -71.6 cmHg, and the mass of the fish ranges from 94 grams to 136 grams. The type of research is quantitative and uses experimental methods. The result is in the form of a remaining moisture content percentage of 40% in dried fish according to SNI standard No. 827300:2023. The Respone Surface Methodology (RSM) was used to process the data in this study. From the study, the best value of vacuum pressure was -66 cmHg and mass 102.5417 with a final result of 40%.